2011
DOI: 10.1111/j.1439-0272.2011.01250.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cystic fibrosis transmembrane regulator and azoospermia factor polymorphisms in infertile men in relation to other abnormalities

Abstract: The aim was to determine the prevalence of compound genetic abnormalities in patients who are carriers of cystic fibrosis transmembrane regulator (CFTR) gene polymorphism and to compare our results with similar patients reported in the literature. One hundred and nine patients were identified to be carriers of CFTR gene polymorphism. Additional genetic testing for karyotype abnormalities or Y chromosome microdeletions (YMD) was performed. Three patients (2.75%) of 109 were identified to have compound genetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…It is well established that Caucasians are more likely to develop classic CFTR disease and show a higher mutation rate, such as 508 mutation, compared with Chinese and other east Asian populations [ 3 ]. A recent study showed that the 5T haplotype is relatively more common compared with fertile controls, indicating that same mutation of CFTR may be shared with different ethnicities [ 6 , 9 , 35 , 36 ]. Several studies have shown that IVF patients have more 5T mutations; therefore it has been recommended that a CFTR mutation screen should be conducted in IVF clinics as routine practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that Caucasians are more likely to develop classic CFTR disease and show a higher mutation rate, such as 508 mutation, compared with Chinese and other east Asian populations [ 3 ]. A recent study showed that the 5T haplotype is relatively more common compared with fertile controls, indicating that same mutation of CFTR may be shared with different ethnicities [ 6 , 9 , 35 , 36 ]. Several studies have shown that IVF patients have more 5T mutations; therefore it has been recommended that a CFTR mutation screen should be conducted in IVF clinics as routine practice.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study and others have found that CFTR is expressed in mouse and human sperm and play important roles in sperm capacitation, however, whether CFTR dysfunction is related to spermatogenesis defects is still unclear [ 3 5 ]. European studies have shown that azoospermia patients have significantly higher 5T mutations compared with oligospermia patients, suggesting CFTR mutations could be related to defective spermatogenesis in humans [ 6 , 7 ]. On the other hand it is known that people from east Asia have a very low incidence of the CFTR mutation related to classic CF disease [ 8 ].…”
Section: Introductionmentioning
confidence: 99%